Analysis of lncRNAs and mRNA Expression in the ZBTB1 Knockout Monoclonal EL4 Cell Line and Combined Analysis With miRNAs and circRNAs - Wang, Junhong; Li, Xiaoxu; Lu, Yiyuan; Huang, Quntao; Sun, Yu; Cheng, Mingyang; Li, Fengdi; Shi, Chunwei; Zeng, Yan; Wang, Chunfeng; Cao, Xin (Frontiers in Cellular and Infection Microbiology, 2021)
In previous experiments we found the effect of deletion of Zbtb1 gene on circRNA and microRNA, in this study we examined the expression profiles of lncRNA and mRNA using RNA-seq method for Zbtb1-deficient EL4 cells, performed clustering analysis of differentially expressed lncRNA and mRNA, and GO term histogram and KEGG scatter plot were drawn. And for the experimental results, a joint analysis was performed, which finally predicted the regulatory relationships among lncRNA, mRNA, microRNA and circRNA. For the regulatory relationship between lncRNA and target genes the chromatin structure and the degree of openness were verified for the possible target gene locations regulated by LNC using experimental methods such as Hi-C and ATAC-seq. Ultimately, the possible differential regulation of the Brcal and Dennd5b genes by lncRNAs and the differential changes in transcription factor binding sites in the promoter region were identified. For neRNA-regulated target genes with significantly differentially expressed mRNAs, a combined screen was performed, and the final obtained candidate target genes were subjected to GO term, KEGG term enrichment analysis. Our results illustrate that the Zbtb1 gene can not only function as a regulatory factor, but also regulate EL4 cells from multiple perspectives based on ceRNA theory.